Heterogeneous ceramide distributions alter spatially resolved growth of Staphylococcus aureus on human stratum corneum. Issue 141 (30th April 2018) - Cleary, Joseph M.; Lipsky, Zachary W.; Kim, Minyoung; Marques, Cláudia N. H.; German, Guy K.
Abstract : Contemporary studies have revealed dramatic changes in the diversity of bacterial microbiota between healthy and diseased skin. However, the prevailing use of swabs to extract the microorganisms has meant that only population 'snapshots' are obtained, and all spatially resolved information of bacterial growth is lost. Here we report on the temporospatial growth of Staphylococcus aureus on the surface of the human stratum corneum (SC); the outermost layer of skin. This bacterial species dominates bacterial populations on skin with atopic dermatitis (AD). We first establish that the distribution of ceramides naturally present in the SC is heterogeneous, and correlates with the tissue's structural topography. This distribution subsequently impacts the growth of bacterial biofilms. In the SC retaining healthy ceramide concentrations, biofilms exhibit no spatial preference for growth. By contrast, a depletion of ceramides consistent with reductions known to occur with AD enables S. aureus to use the patterned network of topographical canyons as a conduit for growth. The ability of ceramides to govern bacterial growth is confirmed using a topographical skin canyon analogue coated with the ceramide subcomponent d -sphingosine. Our work appears to explain the causal link between ceramide depletion and increased S. aureus populations that is observed in AD. It may also provide insight into disease transmission as well as improving pre-operative skin cleansing techniques.